Optimization of Enzyme Dilution Buffer and Reaction Buffer for Vaccinia H-1 Related Wild Enzyme Assay and Its Stability at 4°C - Khadka, Deegendra (Nepal Journal of Science and Technology, 2015)
A human dual specific phosphates (DUSP), Vaccinia H-1 related wild enzyme (VHR), dephosphorylates both phosphotyrosine and phosphoserine/phosphothreonine residue of a protein. VHR is considered as a promising therapeutic target for cancer because the cells lacking VHR are arrested at the G1-S and G2-M transitions of the cell cycle with a decreased telomerase activity. VHR being a therapeutic target for cancer is crucial to know about its stability and its assay procedure conditions. This study was conducted to verify the viability of VHR enzyme at 4°C. Protein concentration and specific activity were calculated from Bradford method and p-nitrophenylphosphate (pNPP) assay by measuring the absorbance at 595 nm and 405 nm respectively in each respective day. The absorbance showed invariable difference in protein concentration and specific activity from starting to final days. Buffers like enzyme dilution and reaction buffers played significant role in VHR enzyme stability and activity. To find out the correct buffer components for carrying out the VHR enzyme assay, several experiments were carried out by using variable constituents in enzyme dilution buffer and reaction buffer. The present study revealed that 3- component buffer system without thiol i.e. Dithiothreitol (DTT) or β-Mercaptoethanol (β-ME) as a reaction buffer and 2-N-morpholino ethanesulfonic acid (MES) buffer with DTT as an enzyme dilution buffer demonstrated invariably different in the stability throughout the experiment. DOI: http://dx.doi.org/njst.v15i2.12127 Nepal Journal of Science and Technology Vol. 15, No.2 (2014) 117-122